Anxiety and depression during pregnancy in women attending clinics in a University Hospital in Eastern province of Saudi Arabia: prevalence and associated factors - Alqahtani AH; Al Khedair K; Al-Jeheiman R; Al-Turki HA; Al Qahtani NH (Dove Medical Press, 2018)
Abdullah H Alqahtani,1 Kholoud Al Khedair,2 Reem Al-Jeheiman,2 Haifa A Al-Turki,2 Nourah H Al Qahtani2 1Department of Psychiatry, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, 2Department of Obstetrics and Gynaecology, College of Medicine, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia Background: Anxiety and depression during the antenatal period is a growing problem with major effects on the mother, the developing fetus, and the neonate.Objectives: To assess the prevalence of anxiety and depression during pregnancy in women attending the hospital for antenatal care and assess the associated factors.Methods: This is a prospective cohort study conducted in the University Hospital of Imam Abdulrahman Bin Faisal University. Anxiety was evaluated using State Trait Anxiety Inventory. Depression was assessed using Edinburgh Postnatal Depression Scale (EPDS).Results: Complete data were available for 575 women. The mean EPDS score was 10.5 (SD 5.5). The prevalence of depression was 26.8%. The mean state-anxiety score was 38.4 (SD 11.4) and mean trait-anxiety score was 38.2 (SD 9.5). The prevalence of anxiety using state-anxiety scale was 23.6%, while using the trait scale it was 23.9%. The risk is higher among unemployed women with history of miscarriage and unplanned pregnancy.Conclusion: Anxiety and depression are common during pregnancy. Keywords: anxiety, depression, pregnancy